Research on the Correlation of Peripheral Blood Inflammatory Markers with PCT, CRP, and PCIS in Infants with Community-Acquired Pneumonia. (17th October 2022) - Li, Linwei; Miao, Hongyun; Chen, Xue; Yang, Shengjie; Yan, Xiaoyong
Abstract : Aims . This study aimsto investigate the relationship between peripheral blood neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), systemic immune-inflammatory index (SII), and procalcitonin (PCT), C-reactive protein (CRP), and pediatric critical illness score (PCIS) in infants with community-acquired pneumonia (CAP). Methods. 100 infants with bacterial CAP admitted to our hospital between January 2021 and December 2021 were selected as the infected group, and another 100 healthy infants who underwent health check-ups at the same time were selected as the control group, and the NLR, PLR, and SII of peripheral blood of infants in both groups and the serum PCT, CRP, and PCIS scores of infants in the infected group were tested. The correlation between NLR, PLR, SII, and PCT, CRP, and PCIS was analyzed by Spearman's analysis. Results. The peripheral blood levels of NLR, PLR, and SII were higher in the infected group than in the control infants (P < 0.05 ). The ROC results showed that the AUCs of peripheral blood NLR, PLR, and SII for the diagnosis of infants with CAP were 0.934, 0.737, and 0.882, respectively. The ROC results showed that the AUCs of peripheral blood NLR, PLR, and SII for assessing the extent of disease in infants with CAP were 0.815, 0.710, and 0.813, respectively, with best cut-off values of 2.05, 98.57, and 823.41; the joint predicted AUC was 0.862. Conclusions . NLR, PLR, and SII were significantly elevated in the peripheral blood of infants with CAP, positively correlated with PCT and CRP, and negatively correlated with PSIC scores, and NLR and SII also have some guiding value in early diagnosis and assessment of the extent of the disease in infants and toddlers with CAP.